Too crowded, don’t go! Understanding the impact of overtourism awareness on intention to recommend a remote destination - Serena Lonardi; Ilenia Confente; Francesco Raggiotto; David D’Acunto (2023)
This research investigates the impact of overtourism awareness on tourists’ intention to recommend a remote destination. It does so by testing the relationship between tourists’ awareness of overtourism during their pre-travel decision phase and their willingness to recommend the destination they visited, including the mediation effect of tourists’ approach reaction level. In addition, the study explores the moderating role of authenticity, investigating the effect of three sub-dimensions, namely objective, constructive, and existential authenticity. Our results show a negative relation between overtourism awareness and tourists’ intention to recommend a remote destination, finding a positive mediation effect of approach action on such relationship. Lastly, results show a positive moderation effect of objective authenticity while no effect of constructive and existential authenticity. The study suggests valuable insights for both scholars and managers operating in the tourism domain.